Qualidade de silagens de milho (Zea mays L.) e cana-de-açúcar (Saccharum spp.) inoculadas com Lactobacillus hilgardii CCMA 0170 - Reis, Camila Branda dos (2015)
In silage lowering the pH and the low oxygen concentration in the silo collaborate to the inhibition of spoilage and pathogenic microorganisms and the forage is conserved as silage. Two experiments were conducted. The first one aimed to evaluate the effect of strain inoculation of Lactobacillus hilgardii CCMA 0170 in corn forage that grew up in water. We used a completely randomized design with factorial arrangement type 2 (with and without silage inoculant) x 4 (opening times) with 3 repetitions. The viable population of L. hilgardii CCMA 0170 inoculated was 6 log CFU g -1 of forage. Were evaluated levels of DM, CHO, FDN and PB, pH values, populations of BAL, yeasts and filamentous fungi, the concentrations of lactic acid, acetic, propionic and butyric acid, ethanol and 1,2 propanediol and the aerobic stability of the silage, after 90 days of fermentation. The corn plant showed DM content of 366.55 g -1 kg MF. The CP and CHO levels are within the recommended (minimum of 70 and 60 g kg -1 DM, respectively). The NDF is within the reported in the literature. BAL and fungal count of the epiphytic microflora are diverging from those found in the literature. The metabolic content present in the forage was similar to that found in the literature, with the exception of ethanol (above found in the literature). The average content of NDF in all opening times, the control silage was 594.44 kg -1 g DM and inoculated silage was 577.78 g kg -1 MS. At the end of silage NDF content was 559.92 g kg -1 DM. DM content reached 362.20 g kg -1 at the end of fermentation. DM losses by effluent reached 1.23%. The CHO content in the inoculated silage reduced to 4.69 g kg -1 DM and in control silage to 1.94 g kg -1 DM at the end of fermentation. The pH value reached 3.75 (inoculated) and 3.84 (control) after 90 days of fermentation. The BAL population in the silages inoculated control and reached 8.58 and 8.60 log CFU g -1 , respectively. The populations of yeasts and filamentous fungi in inoculated silage was reduced less than the minimum detectable 2 log CFU g -1 . The concentration of lactic acid regardless of the opening time, the control silage was 49.33 kg -1 g DM and inoculated silage 59.85 g kg -1 MS, considering the opening times were: 72.46 g kg -1 DM. The concentration of acetic acid reached 12.93 g kg -1 DM in the inoculated silage and 4.92 g kg -1 DM in the control treatment. The final ethanol concentration was 17.33 g kg -1 in MS silage inoculant and 20.36 g kg -1 MS in the control treatment. The concentration of 1,2-propanediol after 90 days of fermentation reached 0.0127 g kg -1 MS. The concentration of propionic acid alcaçou 2.79 g kg -1 DM silage to the final butyric acid concentration reached 1.39 g kg -1 MS. The temperature of the silage inoculated with L. hilgardii CCMA 0170 showed no increase air throughout the above time, unlike the control silage, which 3-day exposure showed 2 ° C above ambient temperature. The average population at the end of aerobic exposure period, the control and inoculated silages, BAL was 7.18 log CFU-1 and 7.63 g UFCG -1 log CFU log yeast 5.6 g -1 and 1, 06 log CFU g -1 and filament fungus 4.83 log CFU g -1 and 1.12 log CFU g -1 , respectively The inoculation of Lactobacillus hilgardii CCMA 0170 improved the quality of corn silage with low humidity. The second experiment was designed to evaluate the silage cane sugar inoculated with Lactobacillus hilgardii CCMA 0170. We used a completely randomized design with factorial type 3 x 4 with four replicates. A viable population of L. hilgardii CCMA 0170 was inoculated 5:06 log CFU g -1 of forage. Were evaluated the contents of DM, CHO, NDF, CP, also the pH values, populations of BAL, yeasts and filamentous fungi, lactic acid concentrations, acetic and propionic, ethanol and 1,2 propanediol. DM content in cane sugar was 384.93 g kg -1 , CHO 160.82 g kg -1 DM, the NDF fractions were 523.32 g kg -1 DM, CP presented content 31.97 g kg -1 MS forage and the pH was 6.32. The count of the epiphytic microbiota was 5 log CFU g -1 BAL, 5.38 log CFU g -1 of yeast and 5.04 log CFU g -1 of filamentous fungi. There were no concentrations of lactic acid, acetic acid and propionic acid, ethanol and 1,2 propanediol. The CHO n silage control content reduced 67.06% in the silage inoculated with 5 log CFU g -1 63.82% and silage with 6 log CFU g -1 to CHO content 55.52%. The pH value reached 3.56. DM content in silage control reached 315.45 g kg -1 DM, silage inoculated with 5:06 g -1 log CFU reached 378.88 and 381.56 g kg -1 , respectively NDF fractions in silage control reached 713.03 g DM kg -1 and silages inoculated 5 and 6 CFU log g -1 and reached 594.38 598.66 kg -1 MS. The percentage of dry matter loss in the control silage reached 29.51%, a 5 log CFU g -1 10.85% and 6 log CFU g -1 11.31%. The control silage, inoculated with 5 and 6 CFU g -1 log presented, respectively, 9.16, 9.54 and 9.53 log CFU g -1 BAL. The population of yeast in the control treatment was reduced to 4.34 log CFU g -1 as silage inoculated 5- and 6-log CFU g -1 BAL reached 2.07 log CFU g -1 . The population of filamentous fungus reached zero. The lactic acid concentration, regardless of the inoculation reached 48.62 g kg -1 MS. The concentration of acetic acid in the silage controls was 2.89 g kg -1 and DM silages inoculated 13.51 g kg -1 MS (5 log CFU g -1 ) and 10.53 g kg -1 MS (log CFU 6 g -1 ). The control silage reached the maximum concentration of 0.44 g kg-1 DM propionic acid and the silages inoculated with 5:06 BAL log g -1 CFU of 1.04 and 3.15 g kg -1 DM, respectively The 1,2-propanediol was not detected in control silages and silages treated 5- and 6-log CFU g -1 BAL concentration was 0.006 and 0.005 g kg -1 MS, respectively The ethanol concentration reached in control silage 90.02 g kg -1 DM and inoculated silagen 25.19 g kg -1 MS (5 log CFU g -1 ) and 5.69 g kg -1 MS (log CFU 6 g -1 ). The inoculation of Lactobacillus hilgardii CCMA 0170 improved the quality of cane sugar silages, independent of the applied rates, mainly due to lower ethanol concentration.